Beyond Crisis to Opportunity: Creating New Meaning in Life after Earthquakes Through the Four Noble Truths - Promchin, Chetnitipath; Bodhisatirawaranggoora, Panachphongphan; Aggadhammo, Phrapalad Thana; Wowong, Sompoch (Journal of Dhamma for Life, 2025)
This academic article aims to present the application of the Four Noble Truths in healing and rehabilitating the lives of earthquake victims by creating new meaning after the disaster. The article analyzes the relationship between suffering caused by natural disasters and the learning process according to the Four Noble Truths, consisting of suffering (Dukkha), the cause of suffering (Samudaya), the cessation of suffering (Nirodha), and the path leading to the cessation of suffering (Magga). This approach leads to psychological resilience and a paradigm shift in living under the concept of turning crisis into opportunity. This article presents a conceptual framework and practical guidelines for applying the Four Noble Truths in community rehabilitation after disasters effectively and sustainably.